Membership, Neighborhood Social Identification, Well-Being, and Health for the Elderly in Chile - Moyano-Díaz, Emilio; Mendoza-Llanos, Rodolfo (Frontiers in Psychology, 2021)
The world’s elderly population is growing, and in Chile, they represent 16.2% of the total population. In Chile, old age is marked by retirement, with a dramatic decrease in income that brings precariousness. Older adults are economically, socially, and psychologically vulnerable populations. This condition increases their likelihood of disengaging from their usual social environment, facilitating their isolation, sadness, and discomfort. From the perspective of social identity, well-being (WB) can be explained by two principles: social groups’ importance for health and people’s psychological identification with those groups. This study analyzes the relationships between belonging to the neighborhood and extra-neighborhood groups and neighborhood social identification with WB. Urban or rural location and gender are measured, and the sample is 1,475 older Chilean adults of both sexes. The results show that the majority are not members of social groups (52%), and the remaining 48%, are members of one or two groups or organizations (42.65%). Only 4.47% belong to three groups or organizations. Those who belong to groups obtain higher scores, emotional mental WB, and positive emotions than older adults who do not belong. Urban and rural older adults have the same level of WB. Membership in close social organizations (neighborhood councils), or distant ones (clubs for the elderly and religious groups), causes different WB associations. Membership in neighborhood councils reduces gender differences in self-assessment of health. This result supports the idea that participation in heterogeneous groups with a shared sense of belonging to the neighborhood is associated with higher well-being and lower perceived loneliness. Social identification with the neighborhood, rather than belonging to the group, had the most widespread impact on WB and health indicators. The variable social identification with the neighborhood was consistently associated with indicators of hedonic WB.